Improving Learning Engagement in Pancasila Education through an Innovative Learning Strategy - Nia Ramadani; Nur Asifa; Indira Almunawarah; Nurul Nurul; Rieke Walla; Trisna Piter Duma; Juwita Crestiani (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2026)
This Classroom Action Research (CAR) aimed to improve learning concentration, cognitive learning outcomes, and students' creative thinking ability in the Pancasila Education subject through an innovative strategy integrating the Jigsaw cooperative learning model, animated videos, and interactive Wordwall gamification. The research was conducted with 24 Grade V students of SDN 5 Salamae during the second semester of the 2025/2026 academic year across two cycles, each consisting of three instructional sessions. Data were collected and analyzed using descriptive quantitative and qualitative techniques. The results showed that student learning activity increased from 60% (Moderately Active) in Cycle I to 84% (Very Active) in Cycle II. The class average score on cognitive tests rose from 72.5 to 80, with classical completeness increasing from 75% to 87.5%, surpassing the Minimum Mastery Criterion of 70. Students' creative thinking ability improved from an average of 63 (54% completeness) to 81 (87.5% completeness), while the teacher's ability to manage student-centered learning rose from 80.9% to 91.7%. These findings indicate that the integration of the Jigsaw model, animated videos, and Wordwall gamification was found to be an effective strategy for improving learning concentration, cognitive outcomes, and creative thinking, and offers a practical solution for strengthening the quality of Pancasila Education learning in line with the Merdeka Curriculum.